Psychosocial Problems Among Healthcare Workers in a Tertiary Care Centre During the COVID-19 Pandemic - A Qualitative Study (Kerala Journal of Psychiatry, 2025)
Background: The COVID-19 pandemic has affected the mental health of healthcare workers (HCWs) engaged in fighting the pandemic, as reported by many quantitative studies. Only a few qualitative studies, mostly conducted online, have explored the psychosocial problems faced by them, especially the residents. This study was done to have an in-depth understanding of psychosocial problems experienced by the HCWs engaged in delivering care to COVID-19 cases in a tertiary care centre.Methods: A qualitative study was undertaken, comprising 11 In-depth Interviews (IDIs) and four Focus Group Discussions (FGDs) with various stakeholders, chosen purposively to ensure representativeness, after obtaining informed consent. Transcriptions of the recorded IDIs and FGDs and translation to English were done. Free-listing, domain identification, coding, and identification of categories and themes were undertaken. A conceptual model was developed. Triangulation of methods and data was ensured.Results: Physical, emotional, behavioral, interpersonal, and interdepartmental problems, worries, apprehensions, social issues, deficiencies, and occupational impairments were the identified themes. Almost all the participants reported emotional problems like anxiety, fear, depression, anger outbursts, etc. All stakeholders experienced physical problems, primarily related to the use of personal protective equipment, and were overwhelmed by the workload and deficiencies in various domains. Social stigma, discrimination, and ostracization were experienced mostly by the nurses, nursing assistants, and attenders. Deficiencies in their academic training were a major concern for the residents.  Conclusion: Various psychosocial problems were common among HCWs engaged in delivering care to COVID-19 patients. The inadequacies of the system and the attitude of the community contributed to these issues.
Keywords: Pandemic; Psychosocial Problems; Qualitative Study; Social Stigma; Academic Deficiencies